Does post-modern societies have to be ethical? - Barroso, Paulo (2018)
I intend to reflect on the implications between individuals and society, starting from the questions "Does post-modern societies has to be ethical?" For this, I suport my paper on the work of Franz Kafka, In The Penal Colony, to represent a social theater of cruelty aesthetics in contemporary societies os post-modernity.